Optimizing the efficiency of organic solar cell under indoor light via controlling optical absorption. (2nd January 2018) - Vincent, Premkumar; Shim, Jae Won; Bae, Jin-Hyuk; Kim, Hyeok
ABSTRACT: Indoor lighting is a major source of energy consumption in buildings. However, reusability of the power output from the light source can help to recycle a small portion of the expended power. Third generation solar cells, such as organic solar cells (OSC), and dye-sensitized solar cells (DSSC), are semi-transparent and can be fabricated on flexible substrates. These desirable characteristics make them suitable candidates to be employed in applications such as smart windows, low-light harvesting systems, and wireless sensor nodes. Illuminance of household lighting is usually in the range of 500 lux. Our researched focused on optimizing the device structure of a conventional OSC to maximize its power conversion efficiency (PCE). When illuminated under a 500 lux light emitting diode (LED) light source. We have integrated optical modelling with empirical fitting of experimental data to conclude the most optimized structure for the low-light harvesting indoor photovoltaic (IPV) device.